Comparison of sequences of hypervariable region (HVR) subunit S-1 gene of field isolate I-37 infectious bronchitis virus with Connecticut serotype - Dharmayanti, N.L.P Indi; Indriani, Risa; ., Darminto (Indonesian Journal of Animal and Veterinary Sciences, 2003)
Infectious Bronchitis is a contagious and acute respiratory disease in chickens caused by infectious bronchitis virus (IBV).Antigenic differences in IBV are associated with changes in the sequence of the spike glycoprotein (S). The subunit S1 which demonstrates more sequence variability than S-2 have been identified as hypervariable region (HVR-1 and 2). There were several IB virus field isolates included I-37 have been identified in Indonesia by serum neutralization method. However, gene sequence variation in HVR subunit S-1 had not yet been identified. Isolate I-37 was close to the serotype Connecticut 46 (Conn 46). The aim of this study is to identify sequence variation of HVR subunit S-1 gene of isolate I-37 produced by Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR) and sequencing. Several procedures were carried out in the study including virus titration, propagation and was concentrated from the allantoic fluid infected with IBV. Then, RNA was extracted for RTPCR. urther the product was sequnced and its homology with IBV references from GenBank was compared by GenMac version 8.0. Result showed that isolate I-37 produced 515 bp of amplification product. Isolate I-37 and Conn 46 are same serotype, yet their HVR subunit S-1 nucleotides and amino acids (protein) differ by 6.9% and 15.6% respectively. It might be concluded that isolate I-37 was variant of Conn 46. Â  Key words: Sequences variation, IBV, I-37 field isolate, HVR subunit S-1 gene